The Effects of Technological Parameters on the Depth of Osmotic Heating and Microhardness for Processing Hard Turning 9XC Steel with Laser Assisted - Nguyen, Thanh Huan; Tran, Xuan Thai; Nguyen, Duc Toan (Old Journal, 2018)
Basic principles of processing hard turnning 9XC steel (62HRC) with Laser Assisted is used laser source to soften the workpiece material before cutting tools during machining. As well as other processing methods, request properties materials of the machine element are not or little changed after processing. The article analyzes the survey results by experiment on the effects of technological parameters such as laser power, feed rates, cutting speeds, depth of cut to to the depth of osmotic heating and microhardness after processing hard turnning 9XC steel with laser assisted. The analysis of the experimental results show that the depth of cut is greater than 0.1 mm, rotation speed greater than 500 rev/min, the microstructure and microhardness of the machine element after processing is not changed.